The patient's right to the medical record of a therapeutic agreement In a human rights perspective - Abdul Kolib (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
Health is a healthy condition, physically, mentally, spiritually and socially that enables everyone to live productively socially and economically. Health is a basic human right guaranteed in the Constitution of the Republic of Indonesia Year 1945, which with this basic right creates an obligation for anyone who organizes Health Services to fulfill that right. Health services are carried out by Health Workers which include medical workers, pharmacy workers, nursing staff, public and environmental health workers, nutrition workers, physical ignorance staff, medical technical personnel, and other health workers, one of which is a Doctor, where the legal relationship between the Doctor and the Doctor Patients are bound by an agreement called a therapeutic agreement that gives birth to the rights and obligations of both parties as the basis of the doctor in providing health services to the patient, and requires the doctor to make a document in the form of a medical record containing facts relating to the patient's health, so that in the journal This focus will be analyzing the patient's right to a medical record as well as the doctor's obligation to the patient's medical record based on human rights. This research has 2 (two) problem formulations: 1) how is the patient's right to a medical record based on human rights?; and 2) what is the doctor's obligation for the patient's medical record based on human rights?. The writing of this journal was conducted using the juridical-normative legal research method, with the support of data in the form of secondary data covering legal materials, as follows: 1) primary legal material, namely the Constitution of the Republic of Indonesia Year 1945, Law No. 36 of 2009 concerning Health, Law No. 29 of 2004 concerning Medical Practices, and Regulation of the Minister of Health of the Republic of Indonesia Number 269 / MENKES / PER / III / 2008 concerning Medical Records; 2) secondary legal materials, namely literature in the form of books, scientific research, journals, etc. related to health law; and 3) tertiary legal materials which include encyclopedias, dictionaries, and so on.